2000
DOI: 10.1007/s002530000357
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of poly(3-hydroxydecanoate): purification and enzymatic characterization of type II polyhydroxyalkanoate synthases PhaC1 and PhaC2 from Pseudomonas aeruginosa

Abstract: For the first time, the purification has been achieved of the type II polyhydroxyalkanoate (PHA) synthases PhaC1 and PhaC2 from Pseudomonas aeruginosa applying N-terminal His6-tag fusions and metal chelate affinity chromatography. In vivo His6-tagged PHA synthase activity was confirmed by functional expression of the corresponding genes in Escherichia coli, and PHA synthase activity could also be measured in vitro with the enzymes. The specific enzyme activity of PHA synthases PhaC1 and PhaC2 was 0.039 U mg(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 19 publications
3
64
0
Order By: Relevance
“…These data suggested that the fatty acid de novo synthesis as well as the ␤-oxidation pathways were involved. It was recently confirmed that the purified PHA MCL synthases from P. aeruginosa exhibit in vitro enzyme activity with (R)-3-hydroxydecanoyl-CoA as the substrate (26). Thus, to serve as a substrate for the PHA synthase, (R)-3-hydroxyacyl-acyl carrier protein [(R)-3-hydroxyacyl-ACP], which is an intermediate of fatty acid de novo synthesis, must be converted to the corresponding CoA-derivative.…”
mentioning
confidence: 92%
“…These data suggested that the fatty acid de novo synthesis as well as the ␤-oxidation pathways were involved. It was recently confirmed that the purified PHA MCL synthases from P. aeruginosa exhibit in vitro enzyme activity with (R)-3-hydroxydecanoyl-CoA as the substrate (26). Thus, to serve as a substrate for the PHA synthase, (R)-3-hydroxyacyl-acyl carrier protein [(R)-3-hydroxyacyl-ACP], which is an intermediate of fatty acid de novo synthesis, must be converted to the corresponding CoA-derivative.…”
mentioning
confidence: 92%
“…The 1.3-kb BamHI-HindIII fragment containing the P. putida phaG gene was isolated from plasmid pBHR75 (14) and subcloned into the respective sites of plasmid pBHR71 (8). The resulting plasmid, pBHR73, was hydrolyzed with XbaI, and a fill-in reaction was performed with the large fragment of DNA polymerase I.…”
Section: Methodsmentioning
confidence: 99%
“…Purified PHA synthase and suitable CoA-activated monomers in an aqueous buffer are sufficient for in vitro synthesis of PHA (17,39,41,78,91). If the metabolism of a given species is able to provide suitable precursor substrates (acyl-CoAs), recombinantly expressed PHA synthase catalyzes the formation of PHA in vivo in different host such as plants, animals, or yeasts (49,72,120).…”
Section: Pha Synthasesmentioning
confidence: 99%